Prognostic impact of the controlling nutritional status score in patients with peripheral T-cell lymphoma. Issue 6 (12th May 2022) - Nakamura, Nobuhiko; Kanemura, Nobuhiro; Lee, Shin; Fujita, Kei; Morishita, Tetsuji; Takada, Eri; Shibata, Yuhei; Kasahara, Senji; Goto, Hideko; Fukuno, Kenji; Hara, Takeshi; Yamada, Toshiki; et al.
Abstract: The controlling nutritional status (CONUT) score is a simplified nutritional index calculated from serum albumin, total cholesterol, and total lymphocyte count. This study evaluated the prognostic impact of the CONUT score on overall survival (OS) in patients with peripheral T-cell lymphoma (PTCL). A multicenter, retrospective cohort study including 99 patients with PTCL was conducted. The CONUT score was significantly higher in the non-survivor group (median 5, range 0-12) than in the survivor group (median 3, range 0-11; p = 0.026). The CONUT score was an independent prognostic factor in a multivariable Cox proportional hazards model (hazard ratio 1.119, 95% confidence interval 1.021-1.227, p = 0.017). No significant effect-modification by the International Prognostic Index (IPI) was observed, and the CONUT score affected the prognosis of PTCL regardless of the IPI ( P for interaction = 0.208). In conclusion, the CONUT score is an independent prognostic factor for PTCL irrespective of IPI category.